Analysis Of Social Responsibility Human Resource Management (Sr-Hrm), Green Lifestyle And Employee Performance Through The Mediation Of Employee Organizational Identification In Mineral Water Companies In Yogyakarta - Syalaisha Putri Dewanti; Muafi Muafi (Eduvest - Journal of Universal Studies, 2025)
This study aims to determine the existence of Social Responsibility Human Resource Management (SR-HRM), Green Lifestyle and the performance of this work has been done well by mineral water companies in Yogyakarta. The population in this study were employees of mineral water companies in Yogyakarta. The results of the online survey using an online questionnaire in the form of a google form and obtained a sample of 150 respondents. In this study using Smart PLS software version 3.2.9 to analyze all data. The variables used in this study such as Social Responsibility Human Resource Management (SR-HRM), Green Lifestyle and Employee Performance through Organizational Identification. The results obtained from this study indicate that Social Responsibility Human Resource Management has an effect on Organizational Identification, Organizational Identification has an effect on Employee Performance, Green Lifestyle has an effect on Organizational Identification, Green Lifestyle has an effect on Employee Performance and Social Responsibility Human Resource Management has an effect on Employee Performance mediated by Organizational Identification.